Stereotipe Negatif Perempuan: Analisis Resepsi Tokoh Tari pada Film Pengabdi Setan 2 - Febriana, Poppy (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2024)
As a form of mass media and new media, film often serves as a medium to convey messages and meanings to audiences. The movie *Pengabdi Setan 2: Communion* is one such medium used to deliver messages, particularly related to female gender stereotypes as portrayed by the character Tari Daryati. This study aims to analyze how the audience receives these messages through reception analysis, which examines various interpretations from different audiences. Five informants were selected using purposive sampling techniques, ensuring diverse backgrounds for this study. Based on the analysis, one informant occupied the Hegemonic-Dominant position, two were in the Negotiated position, and the remaining two were in the Oppositional position. The limitations of this study include the small and homogeneous sample size and the time constraints, which affected the depth of analysis. The researcher recommends that future studies expand the number and diversity of informants to achieve more representative results, as well as incorporate other research methods, such as netnography, to enrich the data and analysis. This would allow subsequent research to provide a deeper understanding of how gender messages in films are received by different audiences and offer insights for further studies in this field.